Trypanocidal activity of quinoxaline 1,4 Di-N-oxide derivatives as trypanothione reductase inhibitors - Chacón-Vargas, Karla Fabiola; Krauth-Siegel, Renate (Molecules, 2017)
Chagas disease or American trypanosomiasis is a worldwide public health problem. In this work, we evaluated 26 new propyl and isopropyl quinoxaline-7-carboxylate 1,4-di-N-oxide derivatives as potential trypanocidal agents. Additionally, molecular docking and enzymatic assays on trypanothione reductase (TR) were performed to provide a basis for their potential mechanism of action. Seven compounds showed better trypanocidal activity on epimastigotes than the reference drugs, and only four displayed activity on trypomastigotes; T-085 was the lead compound with an IC50 = 59.9 and 73.02 µM on NINOA and INC-5 strain, respectively. An in silico analysis proposed compound T-085 as a potential TR inhibitor with better affinity than the natural substrate. Enzymatic analysis revealed that T-085 inhibits parasite TR non-competitively. Compound T-085 carries a carbonyl, a CF3, and an isopropyl carboxylate group at 2-, 3- and 7-position, respectively. These results suggest the chemical structure of this compound as a good starting point for the design and synthesis of novel trypanocidal derivatives with higher TR inhibitory potency and lower toxicity.